Penerapan Model Problem Based Learning Dengan Pendekatan Deep Learning Untuk Meningkatkan Hasil Belajar Siswa Di Kelas VIII SMPN 1 Sakra - Zainul Muhlis; Linda Mistiari; Isro' Wahyuni; Heni Aprilita; Riska Mawalia (Alpatih Harapan Semesta, 2025)
This study aims to improve students' learning outcomes in Social Studies through the implementation of the Problem Based Learning (PBL) model integrated with a Deep Learning approach in Grade VIII students of SMPN 1 Sakra in the 2025/2026 academic year. The deep learning approach is applied to encourage students’ conceptual understanding and higher-order thinking skills, while the PBL model engages students in real-world problem-solving activities to enhance critical thinking, creativity, and active participation in learning. This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 15 students as research subjects. Data were collected using learning achievement tests administered at the end of each cycle, with the success indicator based on the Minimum Mastery Criteria (MMC) score of 75. The results show an improvement in students’ learning outcomes, where the average score increased from 93.33 in Cycle I with 93.33% mastery, to 98 in Cycle II with 100% mastery. Thus, the application of the Problem Based Learning model with a Deep Learning approach is proven effective in improving students’ learning outcomes on the topic “Geographical Conditions and Interaction with Foreign Nations” in Grade VIII of SMPN 1 Sakra.